Prevalence and phenotypic detection of methicillin resistance Staphylococcus aureus between ruminants butchered for humanoid intake and animal handlers in Maiduguri, Nigeria - Gulani, Isa Adamu; Geidam, Yaqub Ahmed; Adamu, Lawan; Lawal, J. R.; Abadam, Falmata Ali (Journal of Advanced Veterinary and Animal Research, 2016)
Objective: The objectives of this study was to investigate phenotypically the prevalence of Staphylococcus aureus and Methicillin Resistance S. aureus (MRSA) in ruminants and animal handlers in Maiduguri, Nigeria. Materials and methods: A total of 937 samples (900 nasal and skin swabs of cattle and 37 humans samples) were collected in Maiduguri metropolis. The samples were inoculated onto mannitol salt agar (MSA) and blood agar, and the cultrue plates were incubated at 37oC for 24 h. The S. aureus colonies showing golden yellow color on MSA were primarily identified as S. aureus, which were then subjected for catalase and coagulase tests. All S. aureus were finally screened for the presence of MRSA on oxalate resistant screening agar (ORSAB) medium. Antimicrobial susceptibility of the MRSA were measured by disc diffusion method. Results: The overall prevalence of S. aureus was 44.3% (n=414/937). The MRSA could be detected in 12.1% (n=113/937) samples. Considerign different species, S. aureus could be isolated from 137 (45.6%), 148 (49.3%) and 119 (39.7%), 11 (29.7%) cattle, sheep, goat and humans, respectively. In ruminants, 27.7% (n-83/300) bulls were positive for S. aureus. Similarly, 10.7% (n=32/300) and 22.3% (n=67/300) were positive for S. aureus in rams and bucks, respectively. On the other hand, 18% (n=54/300), 38.7% (n=116/300) and 17.3% (n=52/300) samples from cows, ewes and does were positive for S. aureus. The highest MRSA could be isolated from ewes (9.3%; n=28/300) follwed by bulls (7%; n=21/300) and bucks (6.7%; n=20/300). In humans, 13.5% (n=5/37) samples were positive for MRSA. Conclusion: S. aureus and MRSA infections in ruminants and animal handlers are documented in this study. The MRSA may exert public health threat to humans. http://doi.org/10.5455/javar.2016.c145